2005
DOI: 10.1111/j.1464-410x.2005.05634.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of penile fracture based on clinical and magnetic resonance imaging findings

Abstract: OBJECTIVETo present our experience with repairing penile fracture, based on clinical and magnetic resonance imaging (MRI) findings. December 2002 and October 2004, 14 men (19-64 years old) presented to our centre with a penile fracture. Two patients had urethral bleeding. MRI was used before surgery in all patients, and the repair comprised a localized longitudinal penile incision in 13 men. This incision was designed according to the tunical tear site and size already depicted by MRI. One case was managed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Some investigators have recommended the use of ultrasound, carvernosography and magnetic resonance imaging to locate the site of the tunical tear before surgery. 8,9,10 However, the positive predictive values in these studies have been shown to be similar to that of history and clinical examination. 11,12 The operative findings in this series confirmed the clinical diagnosis in all cases, including the location of the tear.…”
Section: Discussionmentioning
confidence: 78%
“…Some investigators have recommended the use of ultrasound, carvernosography and magnetic resonance imaging to locate the site of the tunical tear before surgery. 8,9,10 However, the positive predictive values in these studies have been shown to be similar to that of history and clinical examination. 11,12 The operative findings in this series confirmed the clinical diagnosis in all cases, including the location of the tear.…”
Section: Discussionmentioning
confidence: 78%
“…The diagnosis of penile fracture is usually established based on its characteristic history and physical findings [13]. Patients report hearing a snapping sound during the sexual act, followed by immediate pain and penile detumescence, in addition to the emergence of large edemas, hematomas, and penile deformity [14]. However, additional diagnostic imaging modalities can be used for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, MR imaging helped identify 3 cases of painful post-traumatic hematoma (either intracavernosal or outside the tunica albuginea) without disruption of the tunica albuginea, thereby avoiding surgical exploration. [12] Rupture of the dorsal vein of the penis is a rare condition that mimics acute fracture and should be distinguished from rupture with MR imaging. [12] In the present series, we had 1 case of dorsal vein rupture, which was confirmed surgically.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Rupture of the dorsal vein of the penis is a rare condition that mimics acute fracture and should be distinguished from rupture with MR imaging. [12] In the present series, we had 1 case of dorsal vein rupture, which was confirmed surgically. MR images revealed subcutaneous hematoma with intact tunica albuginea.…”
Section: Discussionmentioning
confidence: 99%